MONTESSORI METHOD - Sugdiyona, Valijonova; Sarvara, Najmiddinova (Journal of Creativity in Art and Design, 2024)
This article describes how to increase the self-confidence of children three to twelve years old by using the Montessori method, the role of supportive teachers, and a new way of teaching preschoolers.